Contribution of Social Business Model to Solve Social Issues: Case Study in Bangladesh - Alam, Md Hussin (2023)
According to Muhammad Yunus, the founder of the social business concept, social business is a financially viable entity created only to solve social problems (Yunus, 2009). While the initial expenditures are restored, all additional income is redistributed to further strengthen the organization's social impact. The surpluses produced by the organization earn no profit on money and they reinvested in the business again, thereby adding more value in the distribution of the goods and services provided. Social business is, in reality, an unusual mixture of conventional for-profit organizations (which focus solely on profit and social benefit) and non-profit organizations (Yunus, 2009). While these social businesses have been around for several decades now, in recent years work on this subject has only begun to be investigated. It is also important to remember that social trends deserve attention, and such institutions could operate in various structures (Huffington Post, 2012).
Keywords: Social Business; Social Issues; poverty; unemployment; Social Exclusion and Good Governance